Penitipan Handphone Sebagai Komunikasi Non Verbal Santri PPP Walisongo Desa Cukir Jombang - Robi’ah Machtumah Malayati; Daniel Susilo (Communication, 2020)
The existence of cell phones deposit counters nearby to Pondok Pesantren Putri (PPP) Walisongo became a symbol of stealth resistance from the students against the school rule of not allowing any students to bring cell phones into their Islamic boarding school. They secretly brought their cell phones with them although they realized that some members of the board already knew their behavior. Such resistance was due to the disparity between Kyai’s and students’ views in seeing technology of information and telecommunication integrated in cell phones. In Kyai’s view, the existence of internet was likely to bring negative impacts, while students wanted to have access on technology of information and telecommunication. Thus, a problem arose, that how cell phone deposit counters was considered as a symbol of stealth resistance from students in Islamic Boarding School toward the rule of not allowing any students to bring cell phones into PPP Walisongo Cukir Diwek, Jombang.